Perspectives of Organic Agriculture and Policy Concerns in Nepal - Pokhrel, Deepak Mani; Pant, Kishor Prasad (Journal of Agriculture and Environment, 2009)
Agriculture production worldwide has been intensified with a simultaneous expansion in pesticides,fertilizers and other agro-chemicals use to meet growing peoples' demands for food. Indiscriminate use of agrochemicals has however resulted in several problems such as pests' resistance to pesticides and resurgence due to elimination of natural enemies, toxic residues in food, water, air and soil, degrading soil environment and ecosystem, animal and human health hazards and ultimate economic losses. Realizing the facts, organic farming is becoming popular recently, and there have been growing concerns on its importance and promotion in number of countries irrespective of their stage of development. Consequently, farming system paradigms have now shifted from mere increased production and productivity to resource sustainability and eco-friendly production techniques in their emphasis. Higher cost due to agro-chemicals and resulting environmental losses incurred in conventional agriculture on one side and higher advantages of ecological diversities available in the country on the other have proved that Nepal has high potentialities and comparative advantages of producing quality organic products. A high majority of mountain farmers in Nepal, excluding a few of the agricultural pockets where so-called commercial agriculture has already introduced, do not use any chemicals. Owing to globally increasing trend of demand for organic food, Nepal can benefit from such exports. The government based on some of its policy instruments is also committed to promoting organic farming in the country. However, the instruments are inadequate and not well integrated. Inadequate research, extension services and manpower especially on production and marketing information and input supply have hindered promotion of organic agriculture. Organic product legislation, standardization, certification and infrastructure in such development are also major issues of policy concerns. Key words: Organic-certification; Organic-farming; Organic-standard; Policy; Nepal; etc. The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 103-115